CYP3A4 overexpression enhances apoptosis induced by anticancer agent imidazoacridinone C-1311, but does not change the metabolism of C-1311 in CHO cells - Pawłowska Monika; Augustin Ewa; Mazerska Zofia (Acta Pharmacologica Sinica, 2016)
Monika PAWŁOWSKA, Ewa AUGUSTIN*, Zofia MAZERSKA Department of Pharmaceutical Technology and Biochemistry, Gdańsk University of Technology, 80–233 Gdańsk, Poland Aim: To examine whether CYP3A4 overexpression influences the metabolism of anticancer agent imidazoacridinone C-1311 in CHO cells and the responses of the cells to C-1311. Methods: Wild type CHO cells (CHO-WT), CHO cells overexpressing cytochrome P450 reductase (CPR) [CHO-HR] and CHO cells coexpressing CPR and CYP3A4 (CHO-HR-3A4) were used. Metabolic transformation of C-1311 and CYP3A4 activity were measured using RP-HPLC. Flow cytometry analyses were used to examine cell cycle, caspase-3 activity and cell apoptosis. The expression of pH 6.0-dependent β-galactosidase (SA-β-gal) was studied to evaluate accelerated senescence. ROS generation was analyzed with CM-H2 DCFDA staining. Results: CYP3A4 overexpression did not change the metabolism of C-1311 in CHO cells: the levels of all metabolites of C-1311 increased with the exposure time to a similar extent, and the differences in the peak level of the main metabolite M3 were statistically insignificant among the three CHO cell lines. In CHO‑HR‑3A4 cells, C-1311 effectively inhibited CYP3A4 activity without affecting CYP3A4 protein level. In the presence of C-1311, CHO-WT cells underwent rather stable G2/M arrest, while the two types of transfected cells only transiently accumulated at this phase. C-1311-induced apoptosis and necrosis in the two types of transfected cells occurred with a significantly faster speed and to a greater extent than in CHO-WT cells. Additionally, C-1311 induced ROS generation in the two types of transfected cells, but not in CHO-WT cells. Moreover, CHO‑HR‑3A4 cells that did not die underwent accelerated senescence. Conclusion: CYP3A4 overexpression in CHO cells enhances apoptosis induced by C-1311, whereas the metabolism of C-1311 is minimal and does not depend on CYP3A4 expression. Keywords: anticancer drug; C-1311; CHO cell; CYP3A4; cytochrome P450 reductase; drug metabolism; cell cycle; apoptosis; senescence This work was supported by R&D grant No 014668/009 from the Chemical Faculty of Gdańsk University of Technology. We thank Dr Thomas FRIEDBERG and Dr Roland C WOLF from the Biomedical Research Centre, Dundee, Scotland, UK, for providing the CHO cell lines for this study. We also thank Dr Joanna POLEWSKA from our department for help in the flow cytometry experiments. * To whom correspondence should be addressed. E-mail ewa.augustin@pg.gda.pl Received 2013-05-10 Accepted 203-08-22